Combined effects of ocean acidification and heat waves on the commercially valuable bivalve Callista chione - FORMENTIN, MARTA (2023)
reserved The increasing concentration of CO2 in the atmosphere, due to the consumption of fossil fuels, is causing climatic changes, such as ocean acidification (OA) and marine heat waves (MHW), which represent a threat for several marine species with both an ecological and economical relevance. In this study, the combined effects of OA and MHW were investigated in the bivalve Callista chione using a multibiomaker approach. In an experimental flow-through system, two pH levels (current ambient pH and ambient pH -0.4 as predicted by climate change scenarios) were combined with two temperature conditions (control, corresponding to the ambient temperature of 10°C and MHW corresponding to ambient + 7°C). The effects on immune system-related parameters (total number, morphology, and functionality of haemocytes) and oxidative stress-related parameters (catalase, acetylcholinesterase and butyrylcholinesterase activities, lipid peroxidation and antioxidant capacity), were assessed at the beginning of the experiment, at the end of the MHW and after the recovery. In general, haemocytes number and dimensions were not significantly affected by the experimental factors nor their interaction. The biochemical parameters were instead influenced by the single experimental conditions (such as temperature, pH, and exposure time), with a different pattern depending on the biomarker and the tissue analyzed. The results also demonstrated that there was not a significant interaction between ocean acidification and heat waves. The increasing concentration of CO2 in the atmosphere, due to the consumption of fossil fuels, is causing climatic changes, such as ocean acidification (OA) and marine heat waves (MHW), which represent a threat for several marine species with both an ecological and economical relevance. In this study, the combined effects of OA and MHW were investigated in the bivalve Callista chione using a multibiomaker approach. In an experimental flow-through system, two pH levels (current ambient pH and ambient pH -0.4 ...